Averting AIDS Crises in Eastern Europe and Central Asia : A Regional Support Strategy - World Bank (Washington, DC, 2013)
The Regional Support Strategy is in recognition of the threats that unchecked epidemics of HIV/AIDS and tuberculosis pose to many of the World Bank's client countries. It is an instrument to guide the World Bank's role in the global development agenda, which includes the Declaration of Commitment at a Special Session of the U.N. General Assembly in June 2001. That declaration reaffirmed a pledge made by world leaders to have halted and begun to reverse the spread of HIV/AIDS by 2015. The document provides a unifying framework for the World Bank's work on HIV/AIDS in Eastern Europe and Central Asia. It identifies the potential costs of inaction, the constraints on an effective response, priority actions to resolve such constraints, and the Bank's plans for helping countries do so as part of a multi-institutional effort. HIV/AIDS is fast becoming a threat to health and economic development in parts of Eastern Europe and Central Asia. Despite the dangers, country responses to the epidemic have been patchy and limited by widespread denial. Where actions have been taken to contain the epidemic, they have tended to be pilot efforts on a scale that is too small to make a dent in the overall course of the epidemic. Governments and civil society have started to address the problem, but they need to do much more to avert HIV/AIDS crises in the region.